A compilation of consumers' stories: the development of a video to enhance medication adherence in newly transplanted kidney recipients. (28th December 2015) - Low, Jac Kee; Crawford, Kimberley; Manias, Elizabeth; Williams, Allison
Abstract: Aim: To describe the design, development and evaluation of a consumer‐centred video, which was underpinned by the Theory of Planned Behaviour and it was created to educate newly transplanted kidney recipients about the importance of medication adherence. Background: Kidney transplantation is a treatment whereby medication adherence is critical to ensure long‐term kidney graft success. To date, many interventions aimed to improve medication adherence in kidney transplantation have been conducted but consumers remain largely uninvolved in the interventional design. Design: Qualitative sequential design. Methods: Twenty‐two participants who had maintained their kidney transplant for at least 8 months and three participants who had experienced a kidney graft loss due to non‐adherence were interviewed from March–May 2014 in Victoria, Australia. These interviews were independently reviewed by two researchers and were used to guide the design of the story plot and to identify storytellers for the video. The first draft of the video was evaluated by a panel of seven experts in the field, one independent educational expert and two consumers using Lynn's content validity questionnaire. The content of the video was regarded as highly relevant and comprehensive, which achieved a score of >3·7 out of a possible 4. Results/findings: The final 18‐minute video comprised 15 sections. Topics included medication management, the factors affecting medication adherence and the absolute necessity of adherence to immunosuppressive medications for graft survival. Conclusion: This paper has demonstrated the feasibility of creating a consumer‐driven video that supports medication adherence in an engaging way.